2023
DOI: 10.1097/rd9.0000000000000058
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood transcriptome analysis of patients with ovarian hyperstimulation syndrome through high-throughput sequencing

Abstract: Objective: Ovarian hyperstimulation syndrome (OHSS) is a frequent iatrogenic complication that arises during assisted reproduction and accounts for approximately 30% of all in vitro fertilization cycles. Using high-throughput sequencing, we investigated the peripheral blood transcriptome of patients with OHSS.Methods: Peripheral blood samples were obtained from 15 patients in each of the OHSS high-risk and low-risk groups on the ovum pick-up day. Subsequently, high-throughput sequencing was used to obtain the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…A previous study in transgenic mice highlighted the pivotal effect of PTX3 on innate resistance to pathogens and regulation of inflammation, thus supporting its potential therapeutic role in the management of immunocompromised patients and various inflammatory conditions (Doni et al 2016 ). Peripheral blood transcriptome results in patients with OHSS and subsequent Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway enrichment analyses revealed that differentially expressed genes in high- and low-risk patients were mainly enriched in several pathways, such as the “immune system” (Yan et al 2023 ). The above results indicated that PTX3 could be considered a therapeutic target for high-risk patients with OHSS and highlighted the potential of VD3 as a therapeutic strategy for the aforementioned patients.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in transgenic mice highlighted the pivotal effect of PTX3 on innate resistance to pathogens and regulation of inflammation, thus supporting its potential therapeutic role in the management of immunocompromised patients and various inflammatory conditions (Doni et al 2016 ). Peripheral blood transcriptome results in patients with OHSS and subsequent Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway enrichment analyses revealed that differentially expressed genes in high- and low-risk patients were mainly enriched in several pathways, such as the “immune system” (Yan et al 2023 ). The above results indicated that PTX3 could be considered a therapeutic target for high-risk patients with OHSS and highlighted the potential of VD3 as a therapeutic strategy for the aforementioned patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to VEGFs, the transcriptional induction of Lhcgr, Ptgs2, and several proinflammatory cytokines (e.g., IL-1, IL-6, and TNF-α) have also been related to OHSS (78,(84)(85)(86). Proteomic data using human blood and follicular fluid showed that patients with a high risk of OHSS tended to have higher expression levels of proteins related to inflammation, complement and coagulation cascades, and cell adhesion (87,88). Consistent with these previous findings, our RNA-seq data discovered that follicles cultured with excessive FSH had significantly higher expression levels of Ptgs2, and a number of proinflammatory genes (Figure 7D), suggesting that there are other potential risks factors of OHSS induced by high doses of FSH, such as the high induction of LHCGR, PTGS2, and related PEG2 production.…”
mentioning
confidence: 99%